Perancangan Visual Display Informasi Di Laboratorium Terpadu Universitas Pahlawan Tuanku Tambusai - Syifa Tanjung, Lailatul; Kumala Sari, Resy; Adeswastoto, Hanantatur (Journal of Engineering Science and Technology Management (JES-TM), 2023)
Hazards can occur anywhere and anytime, including when humans are working in the work environment. Workers often forget that there are dangers threatening around them. The need for invitations to workers to be able to maintain occupational safety and health (K3) at work is an effort that is felt to foster a sense of care for oneself and others to avoid danger. The purpose of this research is to design a visual display of information with an ergonomics approach and visual communication in the integrated laboratory of Pahlawan Tuanku Tambusai University. The ergonomics approach is an approach that utilizes information about the nature, abilities and limitations of humans in designing a work system so that humans can live and work on the system properly, namely achieving the desired goals through the work with ergonomic principles. Meanwhile, the visual communication approach is an approach to the concept of communication and the expression of creative power, which is applied in various visual communication media by processing graphic design elements consisting of images (illustrations), letters, colors, composition and layout. From this research, the results are in the form of calculating the width and height of letters that are good for display design at the integrated laboratory at Pahlawan Tuanku Tambusai University based on an ergonomic approach, good typography types for use in display design and display design based on an ergonomic approach and visual communication.